Greenwashing corporativo no cenário brasileiro: uma análise dos fatores externos e internos determinantes - Ramalho, Ana Lídia de Oliveira Silva (2025)
objective of this study was to investigate the internal and external factors within companies that contribute to the reduction of greenwashing practices in the Brazilian corporate environment. Through a descriptive, quantitative, and ex post facto research design, the sample consisted of 71 companies listed on the Brazilian Stock Exchange (Brasil, Bolsa e Balcão - B3), totaling 224 observations from 2018 to 2021. Descriptive statistics and multiple linear regression with unbalanced panel data were performed. The results indicated several internal and external factors that affected greenwashing practices in Brazil. The legal framework for companies with the greatest environmental impact was a factor that positively influenced the practice of greenwashing among the most traded Brazilian companies on the stock exchange. Additionally, a larger board of directors with a higher proportion of independent members also positively influenced greenwashing practices among companies in the IBRX-100 index. However, surprisingly, the influence of these factors was the opposite of what was initially expected. It was hypothesized that these factors would reduce greenwashing practices, but in reality, they seemed to promote them. As additional findings, it was observed that, on average, Brazilian companies in the IBRX-100 exhibited a relatively low level of greenwashing practices. However, it is important to note that more than a third of the companies analyzed, listed in the IBRX-100, engaged in greenwashing practices at some point during the study period. The sectors with the highest averages of greenwashing practices were Oil, Gas, and Biofuels, Basic Materials, Non-Cyclical Consumer Goods, and Industrial Goods. Within these sectors, companies heavily involved in greenwashing practices were identified, with levels approaching the maximum limit set by the index.